A CASE STUDY OF TEACHER’S TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN TEACHING ENGLISH AFTER PANDEMIC - Taufik, Beatrice Ellen; Sudarsono, Sudarsono; Ikhsanudin, Ikhsanudin (Universitas PGRI Sumatera Barat, 2023)
TPACK is the knowledge that teacher should be mastered it is included technological, pedagogical, and content knowledge. This research aims to determine how the teacher implementations TPACK in post-pandemic and examine students’ response toward the implementation of TPACK in post-pandemic at XII MIPA 8 Students in the Academic Year 2022/2023. This research applies a case study design that helps the researcher to collect the data qualitatively such as interview and observation. Moreover, the participants of this research are the one English teacher and 38 students of XII MIPA 8. The findings of the research are the teacher usually prepares the technology tools to engage the students, becomes selective and creative in choosing appropriate media and gains more information about teaching sources with other English teacher. Besides, students’ response towards the implementation of TPACK showed enthusiastically that can be seen from their participation during teaching and learning process. In conclusion, the implementation of TPACK gives enlightenment in teaching at senior high school.